Optimizing Nutrition Care Using Local Food in Malnourished Children with Measles: A Case Study - Alfiyyatunnisa; Pitaloka, Diana Mareta Ida Fitri Ayu (Journal of Local Therapy, 2026)
Introduction: Measles is a viral infectious disease and often accompanied by serious complications in children with malnutrition. Malnutrition and measles have a relationship that worsens each other, so as comprehensive management is needed through integrated nutrition care. Aim: This study aims to describe the application of integrated nutritional care in children with malnutrition and medical diagnosis of measles. Method: The study used a case study design on a 33-month-old inpatient child. Data collection was carried out through anthropometric, biochemical, clinical, and dietary intake assessments, as well as interviews with parents and medical records review during three days of treatment. Results and Discussion: The results of the study showed that the patient experienced acute malnutrition with very low energy and protein intake, accompanied by a clinical condition of measles infection. Nutritional interventions in the form of providing a High Calorie High Protein (HCHP) diet, collaboration with others health workers, and nutrition education to the parents (mother) showed an increase in nutrient intake, improvement in clinical conditions, and early weight gain during the hospitalization period. However, improvements in laboratory parameters have not been seen significantly in a short period of time. Conclusion: Integrated nutritional care plays an important role in supporting patient recovery and needs to be continued on an ongoing basis after the patient is discharged from the hospital.